Medium voltage distribution : protection : CIBSE AM18.3: 2022 (The Chartered Institution of Building Services Engineers (CIBSE), 2022)
This Applications Manual on medium voltage distribution has been produced to help fill the gap in electrical knowledge in respect of how to safely employ medium voltage for the distribution of electrical power. Our aim is to provide an understanding of a number of key aspects at different design and construction stages of a medium voltage (11 kV) power distribution system to buildings. Consideration is given to system design and to the selection and erection of equipment, including the associated practical aspects. It is intended that this Applications Manual will be used by practitioners in conjunction with established international wiring standards and relevant codes of practice. It will also be of interest to designers and authorities who, while not directly concerned with the design or installation of electrical systems, must understand the advice offered to them by specialists. Further, the manual should be of value to those who wish to enhance their knowledge of electrical power and building services engineering.